Sulfur-Based Denitrification in Streambank Subsoils in a Headwater Catchment Underlain by Marine Sedimentary Rocks in Akita, Japan - Hayakawa, Atsushi; Ota, Hitoshi; Asano, Ryoki; Murano, Hirotatsu; Ishikawa, Yuichi; Takahashi, Tadashi (Frontiers in Environmental Science, 2021)
Sulfur-based denitrification may be a key biogeochemical nitrate (NO3−) removal process in sulfide-rich regions, but it is still poorly understood in natural terrestrial ecosystems. We examined sulfur-driven NO3− reduction using streambank soils in a headwater catchment underlain by marine sedimentary rock in Akita, Japan. In a catchment exhibiting higher sulfide content in streambed sediment, we sampled two adjacent streambank soils of streambank I (two layers) and of streambank II (eight layers). Anaerobic long-term incubation experiments (40 days, using soils of streambank I) and short-term incubation experiments (5 days, using soils of streambank II) were conducted to evaluate variations of N solutes (NO3−, NO2−, and NH4+), N gases (NO, N2O), and the bacterial flora. In both experiments, two treatment solutions containing NO3− (N treatment), and NO3− and S2O32− (N+S treatment) were prepared. In the N+S treatment of the long-term experiment, NO3− concentrations gradually decreased by 98%, with increases in the SO42−, NO2−, NO, and N2O concentrations and with not increase in the NH4+, indicating denitrification had occurred with a high probability. Temporal accumulation of NO2− was observed in the N+S treatment. The stoichiometric ratio of SO42− production and NO3− depletion rates indicated that denitrification using reduced sulfur occurred even without additional S, indicating inherent S also served as an electron donor for denitrification. In the short-term incubation experiment, S addition was significantly decreased NO3− concentrations and increased NO2−, NO, and N2O concentrations, especially in some subsoils with higher sulfide contents. Many denitrifying sulfur-oxidizing bacteria (Thiobacillus denitrificans and Sulfuricella denitrificans) were detected in both streambank I and II, which dominated up to 5% of the entire microbial population, suggesting that these bacteria are widespread in sulfide-rich soil layers in the catchment. We concluded that the catchment with abundant sulfides in the subsoil possessed the potential for sulfur-driven NO3− reduction, which could widely influence N cycling in and NO3− export from the headwater catchment.